The distribution of pressure over the surface of wings of small aspect ratio - Marshall, W. S. D. (College of Aeronautics, Cranfield, 1952)
The distribution of pressure over wings of aspect ratio 1.5 and 0.5 have been measure for a range of incidences up to and including the stall at various angles of yaw. This report presents a detailed analysis of the results at two incidences corresponding to ¼ and ¾ of the stalling incidences approximately. Continues …